STANDARISASI VITAMIN C PADA BUAH BENGKUANG (Pachyrhizus erosus) SECARA SPEKTROFOTOMETRI UV-VIS - Harti Widiastuti (Jurnal Fitofarmaka Indonesia, 2015)
Have been conducted by a obstetrical research of vitamin C at juicy tuber by spectrophotometry UV – Vis.  The research aim to determine and compare the content of vitamin C from juicy tuber. Firstly fruit of juicy tuberare cleared by their seed then it weighed after that it enhanced by oxilate acid 0.4% and than it blended and filtered. Filtrat obtained to qualitative analyze by using the react specific and standarization of vitamin C using the spectrophotometry UV – Visible at wave legth 516 nm obtained rate of mean vitamin C that is juicy tuber yaitu 91.97 mg/100g.